Study Kesesuaian Lahan Untuk Pertanian Padi Sawah Beririgasi Di Kecamatan Bayang Kabupaten Pesisir Selatan - Andri Yanto; Hary Febrianto; Veni; Leony (Indonesian Journal of Glasial Geography, 2025)
The research to be conducted is categorized as descriptive research, which is research that describes the research area with quantitative data and field images. The method used is the scoring method, which is to provide a value for each type of research with the aim of knowing the characteristics of land and the level of land suitability in Bayang District. Samples were drawn purposive random sampling which is random sampling based on specific objectives. Of the 17 units of land appointed 6 units of land as a sample with the aim to determine the characteristics and suitability level of irrigated rice paddies in the District Bayang Pesisir Selatan. The results showed the characteristics of irrigated wet rice fields in Bayang Subdistrict from the results of field surveys and the results of laboratory data with the provisions of good criteria, namely those located in nagari pasar baru, nagari tanjung durian Pasa baru, nagari Saweh Pasa Baru, nagari Kapeh Panji Jaya Talaok, nagari Koto Parapak. The suitability of irrigated rice fields in Bayang Subdistrict from the results of field surveys and laboratory data analysis with the provisions of appropriate criteria, namely those located in the village of Pasa Baru, the village of Tanjung Durian Pasa Baru, and while the results of inappropriate data are located in the village of sawah laweh pasa baru, the village of Kapeh panji jaya Talaok, the village of Talaok, the village of Koto Parapak..